Recreational potential and educational opportunities of summer camps for children - Taras Bondar (Pedagogy of Health)
Background and Study Aim. The decline in the health of school-aged children is a cause for concern and necessitates effective solutions. Summer camps can potentially address this negative trend. This study aims to examine the recreational potential and educational opportunities of summer camps and their impact on children's development.